Immunosuppression with generic tacrolimus in liver and kidney transplantation—systematic review and meta‐analysis on biopsy‐proven acute rejection and bioequivalence. (12th February 2020) - Kahn, Judith; Pregartner, Gudrun; Schemmer, Peter
Summary: While rejection prevention with innovator tacrolimus (Tac) is one of the key factors for long‐lasting graft function, the use of generic Tac is still under debate. Thus, we performed a systematic review and meta‐analysis to provide an overview on the current body of evidence for the effect of generic Tac in adult liver (LT) and kidney transplantation (KT) with focus on both biopsy‐proven acute rejection (BPAR) and bioequivalence. A systematic literature search for trials comparing generic versus innovator Tac was conducted accordingly. Seventeen studies (5 LT, 11 KT, 1 LT/KT) including 1412 patients were identified. About 92.9% (13/14; 5/5 LT, 8/9 KT) of studies reported the same or lower BPAR with generics (pooled RR: 0.84, 95% CI: 0.65–1.09); however, de novo studies showed a significantly lower risk with generic Tac (RR: 0.75, 95% CI: 0.63–0.90), whereas conversion studies showed increased risk (RR: 1.93, 95% CI: 1.00–3.70). Bioequivalence was demonstrated primarily in studies on conversion. The current evidence is mostly based on observational data and studies showing some risk of bias. In conclusion, whereas overall there was no significant difference in terms of BPAR, there is some evidence suggesting lower BPAR risk with generic Tac for de novo use.